Keylogger: A Boon or a Bane (Trinity Journal of Management, IT & Media (TJMITM), 2022)
Modern technology, particularly the internet revolution, has greatly improved the  quality of human life. As it has been said that every coin has two sides, so are  security lapses making people more open to assault, one of which can be triggered  or initiated through a keylogger. In this paper Keyloggers, various keylogger types  are discussed. Keyloggers are one of the notable tools that can be used to gather  sensitive or private information from both legitimate and contradictory malicious  users too. These keyloggers are extremely advantageous and are used positively  for monitoring employee productivity, for law enforcement and the search  for evidence of the crime, while it’s negative illegal use includes data theft and  passwords. Software keyloggers that may be simply distributed through email as an  attachment or via a link to play or watch a movie, etc. makes the users vulnerable.  Keyloggers can remain undetected while capturing keystrokes and sending the  details to hackers for planning and executing attack.
Keywords: Malware; Keyloggers; software Keyloggers; hardware Keyloggers; Spyware,; Cyberwarfare